South Korean’s Auto Industry: The Influence Of Design, Fuel Efficiency, Price, Quality, And Technology On US Consumers’ Purchasing Decision - Abdullah Alshboul; Yiming Wang (European Scientific Journal, ESJ, 2016)
The purpose of this quantitative research was to identify whether there were correlations between U.S. automobile consumers’ perceived value and South Korean automobiles’ price, quality, fuel efficiency, design, and technologies. The sample size of the current study was 538. A questionnaire was used to collect data from automobile consumers in 50 states and in the District of Columbia. The results show that consumers’ perceived value were positively related to South Korean automobiles’ price, quality, fuel efficiency, design, and technologies. The result of a multiple regression analysis shows that South Korean automobiles’ quality, fuel efficiency, design, and technologies were significant predictors of consumers’ perceived value. On the other hand, price was only a marginally significant predictor of consumers’ perceived value. In the second multiple regression analysis which considers the participants’ gender, age, education level, and income level, results indicated that none of the four variables had any effect on consumers’ perceived value. Implications for South Korean automobiles’ pricing, quality control, and manufacturing strategy are discussed. Directions for future research are also proposed.